LEDY: An Android Application-Based Learning Media Development to Improve Students’ Writing Skill - Nayohan, Oktania; Yulistianti, Hayu Dian (Universitas Galuh, 2024)
Smartphones can play a pivotal role in enhancing the learning process. Additionally, the multimedia capabilities of smartphones, such as interactive videos and educational games, make the learning process more engaging and enjoyable. The problem by students encompassed a shortage of interactive learning materials, challenges in understanding English content, restricted chances for practical application, and a sense of monotony in the learning process. Therefore, this research aims to design an Android application-basedlearning media, especially on writing skills. This research is a Research and Development (R&D) with the ADDIE model. The subject of this research is tenth-grade students at SMK Wikrama 1 Jepara, with data collected through questionnaires and a pretest-posttest procedure. The effectiveness of the Android application was assessed by using the N-Gain method in analyzing pretest and post-test data. The test outcomes demonstrated an 83.8%success rate, falling within the appropriate category. The pre-test and post-test scores exhibited improvement, with the N-Gain analysis revealing a value of 0.60, signifying enhancementin writing skills. It means that using LEDY an Android application-based learning media, contributes to an improved comprehension among 10th-grade students at SMK Wikrama 1 Jepara, particularly in the area of procedure text material.